RANCANG BANGUN SISTEM INFORMASI PERMINTAAN LAYANAN DALAM LINGKUP DEPARTEMEN IT DI PT CONCORD CONSULTING INDONESIA - Irma Yunita Ruhiawati; Dadang Amiruddin; Yul Hendra; Ely Nuryani; Nanang Wahyudi (LPPM Unbaja, 2026)
In the digital era, information technology plays a vital role in supporting business operations. Effective IT service management is essential for improving work efficiency and employee productivity. PT Concord Consulting Indonesia, an information technology consulting firm, faces challenges in managing internal IT service requests, which are still handled manually through emails, instant messaging applications, and direct communication. This unstructured process leads to several issues, such as difficulties in tracking request statuses, lack of systematic documentation, absence of clear prioritization mechanisms, and unclear task distribution. This study aims to design and develop a web-based information system for managing IT service requests to support a more organized, well-documented, and transparent process. The implementation of this system is expected to accelerate service resolution, enhance operational efficiency, and improve coordination among teams within the IT Department.